Investigation of zinc(II) adsorption on Cladophora crispata in a two-staged reactor - Özer, D; Özer, A; Dursun, G (John Wiley & Sons Ltd, 2000)
In this study, the adsorption of zinc(II) ions on Cladophora crispata, a green alga, was studied with respect to initial pH, temperature, initial metal ion and biomass concentration in order to determine the optimum adsorption conditions. Optimum initial pH values for zinc(II) ions were found to be 5.0 at optimum temperature, 25 degrees C. The initial adsorption rates increased with increasing initial zinc(II) ion concentration up to 100 mgdm(-3). The Freundlich and Langmuir adsorption isotherms were developed at various initial pH and temperature values. Then, the adsorption of zinc (II) ions to C crispata was investigated in a two-staged mixed batch reactor. The residual metal ion concentrations (C-eq) at equilibrium at each stage for a given quantity of dried algae (X-o)/volume of solution containing heavy metal ion (V-o) ratio were calculated by using Freundlich and Langmuir isotherm constants, it was observed that the experimental biosorption equilibrium data for zinc(II) ions are in good agreement with those calculated using both Freundlich and Langmuir models. The adsorbed zinc(II) ion concentration increased with increasing X-o/V-o ratios while the adsorbed metal quantities per unit mass of dried algae decreased. (C) 2000 Society of Chemical Industry.
Keywords: adsorption; isotherm; waste water; multi-staged reactor